Leading a Library Restructure in a Cross-Cultural Organisation: A Vietnam University Library Case Study. Issue 3 (3rd July 2017) - O'Dwyer, Clare Patricia; Nguyen, Loc Huu; Churchill, Andrew C.
Abstract: In 2015, a solely owned Australian international university library in Vietnam underwent major changes that included a new staff structure. At the beginning of the year, an Irish-Australian Senior Library Manager was newly appointed to manage a team of Vietnamese library staff. The library service was reviewed and restructured to better align with the organisation's strategic objectives in relation to research, learning and teaching. The challenges in leading and managing a library restructure in a cross-cultural context are examined from both Eastern and Western leadership perspectives. This case study illustrates that although cultural differences can be perceived, similarities in effective leadership and management are key to implementation success.